Planning and managing change - Payne, Vivette (American Management Association, 2005)
Organizational change can be difficult. The ability to manage change has become a key competency for those seeking to enhance either personal or corporate efficiency and effectiveness. Planning and Managing Change provides a structured and practical approach to dealing with change. This book teaches the importance of proactively managing change and avoiding the knee-jerk reactions that undermine efforts to deal with the organizational and human issues that accompany change. Readers will learn how to: Manage the process, content and human dynamics of change Help others move successfully throu.